Practical optical dimensional metrology - Harding, Kevin G. (SPIE, 2019)
Practical Optical Dimensional Metrology provides basic explanations of the operation and application of the most common methods in the field and in commercial use. The first half of the book presents a working knowledge of the mechanism and limitations of optical dimensional measurement methods that use: light level changes, two-dimensional imaging, triangulation, structured-light patterns, interference patterns, optical focus, light characteristics such as polarization, and hybrid methods with mechanical or other measurement tools. The book concludes with a series of manufacturing application examples that look at measurements from the centimeter range down to the nanometer range.
Title from PDF title page (SPIE eBooks Website, viewed 2018-12-19).
Keywords: Optical measurements.; Metrology.; elektronické knihy; electronic books